Risky dieting amongst adolescent girls: Associations with family relationship problems and depressed mood. (August 2016) - Hinchliff, Gemma L.M.; Kelly, Adrian B.; Chan, Gary C.K.; Patton, George C.; Williams, Joanne
Abstract: Objective: This study examined the association of risky dieting amongst adolescent girls with depressed mood, family conflict, and parent-child emotional closeness. Method: Grade 6 and 8 females (aged 11–14 years, N = 4031) were recruited from 231 schools in 30 communities, across three Australian States (Queensland, Victoria, and Western Australia). Key measures were based on the Adolescent Dieting Scale, Short Mood and Feelings Questionnaire, and widely used short measures of family relationship quality. Controls included age, early pubertal onset, and socioeconomic status. Results: Risky dieting was significantly related to family conflict and depressed mood, depressed mood mediated the association of family conflict and risky dieting, and these associations remained significant with controls in the model. Conclusion: Family conflict and adolescent depressed mood are associated with risky dieting. Implications: Prevention programs may benefit from a broadening of behavioural targets to include depressed mood and family problems.